Effect of electrolytes on redox reactivity of polypyrrole - Kim, DY; Kim, JK; Lee, JY; Rhee, HW; Kim, CY (JOHN WILEY & SONS LTD, 1997)
Doping and dedoping characteristics of polypyrrole (PPy) formed electrochemically have been examined by means of energy-dispersive X-ray spectroscopy (EDS). Dodecylsulfate ions (DS-) and perchlorate ions (ClO4-) were embedded simultaneously in PPy when both ions were present on the polymerization of pyrrole. Sequential formation of PPy in the single dopant system allowed PPy/ClO4 to grow in the bulk of PPy/DS but not vice versa. DS- was embedded not to leave the polymer on reduction but ClO4- moved in and out of the polymer on redox reaction. Cyclic voltammetry was Employed to determine the redox reactivity of PPy in different electrolyte systems. NaClO4 was a better electrolyte for cyclic redox reaction than LiClO4 or KClO4. NaCl was a good electrolyte fo. cyclic redox reaction but Cl- failed to penetrate in the PPy/DS bulk on reoxidation. The cyclic redox reactivity lasted longest when PPy/DS teas redox-cycled sequentially in the NaCl electrolyte system and then in the NaClO4 system. (C) 1997 by John Wiley & Sons, Ltd.